Synthesis of 3-chloro-6-((4-(di-tert-butyl[18F]fluorosilyl)-benzyl)oxy)-1,2,4,5-tetrazine ([18F]SiFA-OTz) for rapid tetrazine-based 18F-radiolabeling - Zhu, Jun; Wängler, Carmen; Wängler, Björn (Chemical communications, 2015)
An efficient method to prepare the 18F-labeled tetrazine-derivative [18F]-SiFA-OTz for bioorthogonal radiochemistry was developed. [18F]-SiFA-OTz can be synthesized with a radiochemical yield of 78 ± 5% within 25 min and can quantitatively react with a model strained dienophile, trans-cyclooctenol.
Gesehen am 31.08.2017